Drivers and decoupling situation analysis of Jiangxi's carbon emission. Issue 3 (May 2019) - Jia, Junsong; Song, Xu; Ju, Min; Lei, Jing
Abstract: Using the logarithmic mean Divisia index (LMDI) and Tapio model, we decomposed the drivers of carbon emissions (CE) from energy consumption (EC) in Jiangxi and analyzed the decoupling between economic growth and the CE during 2002-2017. The results showed that economic level effect was the decisive driver for the CE's increase. It brought about a cumulative contribution rate of 206.96% to the CE. Population size effect followed it, with the cumulative contribution rate of 9.58%. However, energy intensity had an obviously negative effect with the cumulative contribution rate of -114.34%. Energy structure had also a negative but not obvious effect with the cumulative contribution rate of -2.20%. Overall, a weak decoupling relationship between economic growth and total CE existed within the Jiangxi in 2002-2017. Namely, the economic development of Jiangxi was transformed into the low-carbon pattern, to a certain extent. Nevertheless, this pattern needed to be continually encouraged and strengthened. Therefore, it was necessary to take some measures to save energy or to reduce emissions while pursuing economic development. Especially, we should continue to improve energy efficiency through technological innovation, to adjust the energy consumption structure and to enlarge the proportion of clean energy, etc., in the long run.